Non‐invasive diagnosis of cirrhosis and long‐term disease monitoring by transient elastography in patients with Wilson disease. (22nd January 2020) - Paternostro, Rafael; Pfeiffenberger, Jan; Ferenci, Peter; Stättermayer, Albert F.; Stauber, Rudolf E.; Wrba, Fritz; Longerich, Thomas; Lackner, Karoline; Trauner, Michael; Ferlitsch, Arnulf; Reiberger, Thomas; Weiss, Karl Heinz
Abstract: Background & Aims: The value of liver stiffness measurement (LSM) by transient elastography (TE) for non‐invasive fibrosis staging and disease monitoring has not been established in patients with Wilson disease (WD). Methods: Liver stiffness measurement by TE and non‐invasive fibrosis scores (APRI, FIB‐4) were analysed from 188 WD patients with liver biopsy (LBX). Longitudinal LSM was performed in 128 (68.1%) patients. Results: One hundred and eighty‐eight patients (mean age: 35 ± 14 years, 54.8% women; 27.1% with histological cirrhosis) were studied. Forty‐four[23.4%] patients were recently diagnosed with WD, while 144[76.6%] were previously diagnosed (>1 year between LBX and LSM). Overall, LSM (11.3 vs 6.1 kPa, P < .001), APRI (0.72 vs 0.38, P < .001) and FIB‐4 (1.54 vs 0.89, P < .001) were higher in cirrhotic than in non‐cirrhotic patients. This was even more pronounced in recently diagnosed patients (35.2 kPa vs 6.4 kPa, P < .001). Accuracy for diagnosing cirrhosis at an LSM cut‐off ≥9.9 kPa was better in recently diagnosed (PPV: 74%, NPV: 100%) vs previously diagnosed (PPV: 53%, NPV: 82%) patients. Recently diagnosed patients had higher Area Under the Curve (AUC) for APRI (0.79 vs 0.61) and FIB‐4 (0.84 vs 0.65) than previously diagnosed patients. At APRI <1.5 and FIB‐4 <3.25 cirrhosis was ruled out with a specificity of 93% and 95% respectively. During a median follow‐up of 46 (24‐66) months, only 5.9% (5/85) of non‐cirrhotic WD patients showed progression to cirrhotic LSM values, while 30.8% (4/13) of cirrhotic WD patients showed LSM suggestive of cirrhosis regression. Conclusion: TE‐based LSM ≥9.9 kPa accurately identifies cirrhosis in WD patients. Next to TE‐LSM <9.9 kPa, APRI <1.5 and FIB‐4 <3.25 values assist to non‐invasively rule out cirrhosis. LSM remains stable in most non‐cirrhotic patients on WD therapy, while one‐third of cirrhotic patients present clinically relevant decreases in LSM.